I found the island, I own the land - Mohamad, Nor Asiah (2010)
There are many disputes as to the ownership of islands which are located at the border of the states. The general principle under the Malaysian land law is all land belongs to the state except alienated land or reserve land. This paper discusses the issue of island whether any individual may claim that he is the owner of the land as he happens to be the first person who occupies the land. Another issue relating to this principle is that can any state claim she is the owner of any island as she happens to be the first states whose people has occupied the island or who happens to rule the island. This paper seeks to discuss the issues from the Islamic land ownership perspective as well as discussing the problem within the contect of the Malaysian land law. Specifically this paper discusses the viability of the application of the principle of ihya al mawat to the issue of new deserted land or islands.